Poly-anthraquinone sulfide isomers as electrode materials for extended operating temperature organic batteries. Issue 1 (9th December 2020) - Flamme, Benjamin; Jismy, Badr; Abarbri, Mohamed; Anouti, Mérièm
Abstract : Three polyanthraquinone sulfide (PAQS ) isomers were synthesized, characterized and included in a comparative study of electrochemical performances as organic material cathodes. Abstract : Three polyanthraquinone sulfide (PAQS ) isomers were synthesized, characterized and included in a comparative study of electrochemical performances as organic material cathodes. The performances of the 1, 5-PAQS, 2, 6-PAQS, and 1, 8-PAQS isomers were compared as a function of charge density, long-term stability and operating temperature. The results obtained showed superior performances for polymers that offer the best spatial flexibility, thus allowing the carbonyl groups to be more accessible to Li cations. The performances (200 mA h g −1 at 4C) of 1, 5 and 2, 6-PAQS isomers were preserved for up to 1000 cycles. The more flexible 2, 6-PAQS isomer demonstrated a remarkable ability to endure fast cycling from 60 °C to −30 °C without a significant decrease in capacity retention (which decreased from 98.1% to 93.4%) thanks to its flexible structure. The reduced effect of the temperature on long term cycling results obtained with 2, 6-PAQS allows it to deliver an energy density of 275 W h kg −1 at −30 °C. It therefore appears that, thanks to their low cost, environmental benignity and high sustainability, the selected PAQS isomers are promising candidates for alternative electrode materials in full-organic batteries dedicated to low temperature operation.